2016
DOI: 10.4209/aaqr.2016.04.0168
|View full text |Cite
|
Sign up to set email alerts
|

Atmospheric PM2.5 and Depositions of Polychlorinated Dibenzo-p-dioxins and Dibenzofurans in Kaohsiung Area, Southern Taiwan

Abstract: Kaohsiung County, in southern Taiwan, has both highly industrial and rural areas. In this study, the characteristics of PCDD/Fs in the ambient air of Kaohsiung (urban), Meinong (rural) and Xiaogang (heavy industrial zone) in 2014 and 2015 were modeled based on the prevailing meteorological conditions and the measured ambient air concentrations of PM 2.5 , PM 10 and TSP. The yearly average PM 2.5 concentrations in the ambient air of the three areas were in the range of 23 to 31 µg m -3 , all above the National … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
40
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(45 citation statements)
references
References 38 publications
5
40
0
Order By: Relevance
“…Low-chlorinated congeners are less adsorbed on graphite than high-chlorinated congeners. Relative study (Lee et al, 2016) also showed that higher chlorinated PCDD/Fs are much easier captured by particle. Probably, vapour pressure plays a dominant role (Karademir et al, 2004;Hung et al, 2011;Ji et al, 2014;Yu et al, 2016a).…”
Section: The Effect Of Adsorption Temperature On the Removal Pcdd/fsmentioning
confidence: 92%
See 1 more Smart Citation
“…Low-chlorinated congeners are less adsorbed on graphite than high-chlorinated congeners. Relative study (Lee et al, 2016) also showed that higher chlorinated PCDD/Fs are much easier captured by particle. Probably, vapour pressure plays a dominant role (Karademir et al, 2004;Hung et al, 2011;Ji et al, 2014;Yu et al, 2016a).…”
Section: The Effect Of Adsorption Temperature On the Removal Pcdd/fsmentioning
confidence: 92%
“…High temperature provides high vapour pressure of PCDD/Fs, and gas phase of PCDD/Fs was found to increase with the increase of temperature. Hence more PCDD/Fs molecules would probably evaporate to the gas phase and escape un-adsorbed as temperature increase (Zhao et al, 2012;Lee et al, 2016). On the other hand, adsorption is an exothermic process, RE of dioxin by graphite would decrease as the temperature increases (Hung et al, 2011).…”
Section: The Effect Of Adsorption Temperature On the Removal Pcdd/fsmentioning
confidence: 99%
“…Such strong surge poses serious risks to both human health and the natural environment, given the considerable emissions of dust, and a host of organic and inorganic pollutants (Cheruiyot et al, 2016;Lee et al, 2016;Li et al, 2016a;Xu et al, 2018). During conventional cement production Thuong et al, 2014) polychlorinated dibenzo-p-dioxins and dibenzofurans (PCDD/Fs) emerge at the level of 0.99 µg I-TEQ ton -1 clinker.…”
Section: Introductionmentioning
confidence: 99%
“…Due to small-scale incinerator, incomplete incineration and high chlorine content in the waste feed, some toxic persistent organic pollutants are generated such as polychlorinated dibenzo-p-dioxins and polychlorinated dibenzofurans (PCDD/Fs), polycyclic aromatic hydrocarbons (PAHs), chlorobenzenes (CBs), chlorophenols (CPs) and polychlorinated biphenyls (PCBs), etc. (Lee et al, 2003;Chen et al, 2013;Cheruiyot et al, 2015;Lee et al, 2016). The PCDD/F emission factors of hospital solid waste incinerator (HSWI) were about 1-2 orders higher than those of municipal solid waste incinerator (MSWI) (Lee et al, 2003;Cheruiyot et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…The principle of flotation is based on the differences in surface hydrophobicity between the particles. The hydrophobicity and lipophilicity nature of PCDD/Fs and other organic contaminants such as PAHs, CBs, CPs and PCBs makes them easy to float into the froths after flotation (Cheruiyot et al, 2015;Lee et al, 2016). The previous report indicated that the flotation process could be successfully applied to substantially decrease the amount of carbon constituents and PCDD/Fs in HSWI fly ash (Liu et al, 2013).…”
Section: Introductionmentioning
confidence: 99%